The last isle : contemporary film, culture and trauma in global Taiwan - Ma, Sheng-mei (Place, memory, affect., 2015)
Explores the affective toll of Taiwan's geographical and political proximity to China through a critical analysis of contemporary Taiwanese film and culture. It examines the complex, precarious relationship between the sovereign state of Taiwan and China in order to consider what this might mean global anxiety around the growing power of China.